2022
DOI: 10.1155/2022/2980250
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Poor Treatment Adherence among Patients with Type 2 Diabetes and Limited Health Literacy: A Scoping Review

Abstract: Prevention of complications and successful control of diabetes require preventive and therapeutic measures. Patients’ nonadherence to medication and diet regimens and healthcare protocols is associated with significant therapeutic and economic consequences. The present scoping review aims to identify determinants of poor treatment adherence among patients with type 2 diabetes and limited health literacy in 2021. This scoping review was conducted in five stages: designing a research question, searching and extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 33 publications
(45 reference statements)
0
10
0
4
Order By: Relevance
“…La misma tiene una (6) relación directa con el conocimiento que tiene el paciente sobre la medicación antidiabética . Otras causas de escasa adherencia son los problemas económicos, la mala comunicación con el equipo de salud, la falta de apoyo familiar, el bajo nivel de conocimientos, la presencia de conceptos erróneos y (13,16) la alfabetización limitada en salud . En Chile se ha visto que los adultos mayores con diabetes (1) tienen mala adherencia en relación al bajo nivel socioeconómico y educativo .…”
Section: Discussionunclassified
See 3 more Smart Citations
“…La misma tiene una (6) relación directa con el conocimiento que tiene el paciente sobre la medicación antidiabética . Otras causas de escasa adherencia son los problemas económicos, la mala comunicación con el equipo de salud, la falta de apoyo familiar, el bajo nivel de conocimientos, la presencia de conceptos erróneos y (13,16) la alfabetización limitada en salud . En Chile se ha visto que los adultos mayores con diabetes (1) tienen mala adherencia en relación al bajo nivel socioeconómico y educativo .…”
Section: Discussionunclassified
“…Los datos obtenidos de esta investigación permiten conocer aspectos del tratamiento de una enfermedad crónica prevalentes en el país y aplicar medidas correctivas pues muchos de esos (13) resultados son modificables . Los estudios demuestran que las mejores estrategias para mejorar el cumplimiento terapéutico tienen que ser mixtas.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…This includes cultural and conceptual knowledge; the ability to listen and speak (for example, following verbal directions); the ability to write and read (for example, reading and understanding labels on pill bottles, medical directions, education brochures, and other T2DM-related information), and the ability to understand and use numbers (for example, comprehending and following medication dosing, test results, food intake, and exercise levels) [ 59 ]. Previous research has shown the relationship between T2DM health literacy, self-management behaviors, and diabetes-related outcomes, such as medication adherence [ 60 ], physical activity [ 61 , 62 ], healthy diet [ 63 ], self-monitoring of blood glucose [ 64 ], and glycemic control [ 59 , 61 , 62 ]. As a part of T2DM health literacy, improving dietary knowledge and skills may change eating patterns, which in turn can affect glycemic control [ 65 , 66 , 67 ].…”
Section: Discussionmentioning
confidence: 99%